APLIKASI PUPUK KALIUM DAN N- BALANSER PADA BUDIDAYA BAWANG MERAH (Allium ascalonicum L.) DI LAHAN PASIR PANTAI - Nur Faizah R; Sumarwoto . (Universitas Pekalongan, 2010)
The experiment of giving potassium fertilizer into several dosesses and concentration of N-Balanser aims to collect doses of potassium KNO3 fertilizer and concentration of N-Balanser liquid organic fertilizer in approppiate amount. It is done to give best plant growth and result of bulb Shallot Plantation (Allium ascalonicum L.). This experiment was conducted on July until September 2009 at Sandy Coastal with inceptisol soil type which located at Tegalrejo, Srigading, Sanden, Bantul, Yogyakarta on 5 m above sea level. The experiment uses Complettely Randomized Block Design Factorial with two treatments factor and three replications. The first treatment factor is potassium fertilizer doses (consists of three levels: K1 =350 kg ha-1, K2 = 400 kg ha-1,and K3 = 450 kg ha-1) and second treatment factor that is concentration of N-Balanser (consists of four levels: N-b1 = 0 ‰, N-b2= 2 ‰, N-b3 = 4 ‰, and N-b4 = 6 ‰).The result of experiment shows that there is unsignificant interaction on all observed parameters between doses of potassium and concentration of N-Balanser fertilizer. The potasium KNO3 fertilizer with doses of 450 kg ha-1 gives vegetatif growth (plant height and leaf amount) and the best result of bulb yield among others. Moreover, the N-Balanser organic fertilizer with concentration of 2‰ already give better result in improving bulb yield and quality. Keywords: Shallot (Allium ascalonicum L.), potassium, N-balanser, sandy coastal